Antibiotic Vulnerability Response Of Avian Pathogenic E.Coli Serotypes From Small And Large Poultry Farms Of Nagpur - Nimbarte, Seema; Kulkarni , Archana (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was undertaken to establish the correlation between serogroups of Escherichia coli and to unreveal their antibiotic vulnerability response. A total of eighty seven avian pathogenic Escherichia coli (APEC) strains were examined for studying their vulnerability response to antimicrobials of veterinary and human significance. 73 APEC isolates belonged to thirteen different serogroups and the rest were untypable. Antibiogram profiles indicated 100% resistance to ampicillin, nalidixic acid, ofloxacin and nitrofurantoin, 96% to norfloxacin, 92% to ciprofloxacin, 88% to tetracycline, 80% to oxytetracycline and 60% to chloramphenicol. The isolates were sensitive to amikacin (100%), gentamycin (64%), streptomycin (96%), colistin (76%), cephalexin (76%) and ceftazidime (76%). These findings confirm that most of the isolates were resistant to five or more antimicrobials. Hence this empirical treatment to reduce the emergence and spread of resistant strains requires constant updating of the antibiotic vulnerability of the main etiological agent of that area, region or country.
Keywords: Antibiotic vulnerability; serotypes; colibacillosis; APEC